2013
DOI: 10.1007/s10147-013-0639-1
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of Mdm2 expression and prognosis of breast cancer

Abstract: Concurrent nuclear and cytoplasmic Mdm2 expression was an independent prognostic factor in patients with breast cancer. Subcellular localization of Mdm2 expression should be considered in the evaluation of Mdm2 in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…MDM2 protein levels have been identified as an independent prognostic biomarker in human BrC [(Park et al, 2014) and reference within it]. Abnormally high levels of MDM2 protein have been measured in at least 1/3 (38%) of human BrCs, which could not be explained by gene amplification alone (Yu et al, 2014).…”
Section: Disruption Of the Mdm Family Occurs In Brcmentioning
confidence: 99%
“…MDM2 protein levels have been identified as an independent prognostic biomarker in human BrC [(Park et al, 2014) and reference within it]. Abnormally high levels of MDM2 protein have been measured in at least 1/3 (38%) of human BrCs, which could not be explained by gene amplification alone (Yu et al, 2014).…”
Section: Disruption Of the Mdm Family Occurs In Brcmentioning
confidence: 99%
“…A total of 291 patients with breast cancer at stage IV upon initially diagnosis, made between January 2001 and July 2014, were identified using the Severance breast cancer registry and the Severance metastatic breast cancer registry. The Severance breast cancer registry is a prospectively maintained database, described previously . In brief, the database includes information on the sex, age at the time of the diagnosis of stage IV breast cancer, T stage, nodal status, estrogen receptor (ER)/progesterone receptor (PR) status, human epidermal growth factor receptor 2/neu (HER2) amplification, tumor grade, and tumor subtype.…”
Section: Methodsmentioning
confidence: 99%
“…HER2 staining was considered positive in cases with an IHC score of 3+ or gene amplification as seen by fluorescence in‐situ hybridization (FISH), regardless of the HER2 IHC result. FISH analysis for HER2 was analyzed as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDM2 promotes tumor formation by targeting tumor suppressor genes (e.g., p53 and p16), and its overexpression has been detected in a variety of different cancers [37]. Okamoto et al [38] reported that MDM2 positivity in pretreatment biopsy specimens was significantly higher in the failure group than in the CR group among cStageIII ESCC patients treated with definitive CRT.…”
Section: Negative Biomarkers In Tissue Examinationmentioning
confidence: 99%